قواعد التحريم في المعاملات المالية الإسلامية = Rules of prohibition in Islamic financial - Daqqaq, Mahmoud Abdulrahman; Arif, Arif Ali (IIUM Press, International Islamic University Malaysia, 2019)
تهدف هذه الدراسة إلى بيان القواعد التي بنيت عليها المعاملات المالية المحرمة في الشريعة الإسلامية؛ حيث تكلم العلماء سابقاً عنها لكنهم اختلفوا فيها، واختلافهم ناتجٌ عن تعدد اجتهاداتهم في بعض المعاملات؛ كونها تحتمل الرجوع إلى قاعدة دون أخرى، أو لكون بعض القواعد تلحق بقواعد أخرى نتيجة توسعهم في مفهوم تلك القواعد. وسيقوم الباحث بعرض أقوال علماء الشريعة الإسلامية في قواعد التحريم للمعاملات المالية ومناقشتها، ثمَّ تأطير قواعد فقهية تجمع ما قاله العلماء السابقون في قالب واحد؛ ممَّا يسهل دور علماء الشريعة عند النظر في المعاملات المالية التي يستحدثها علماء الاقتصاد أو أفراد الناس؛ حيث سيستطيع العلماء الحكم على هذه المعاملات بعد عرضها على قواعد المعاملات المحرَّمة في الشريعة الإسلامية بالصحة أو البطلان. ******************************************************* The purpose of this thesis is to explain the rules on which the forbidden financial transactions are based in the Islamic Shari'ah The earlier scholars have addressed these rules but differed in relation to them. This is due to the diversity in their juristic opinions regarding some transactions, since it is possible to follow a certain rule rather than another one, or because some rules are ajuncted to other rules as a result of the expansion in the concept of those rules. The purpose of this thesis is to explain the rules on which the forbidden financial transactions are based in the Islamic Shari'ah. The earlier scholars have addressed these rules but differed in relation to them. This is due to the diversity in their juristic opinions regarding some transactions, since it is possible to follow a certain rule rather than another one, or because some rules are ajuncted to other rules as a result of the expansion in the concept of those rules.